Freeze-thaw stability of frozen buco pie - Santos, Michelle Geronaga
The study was conducted to determine the freeze-thaw stability of buko pie. Eighteen buko pie samples were subjected to 16 hours of freezing at -13.3°C. After freezing, the samples were thawed for another 8 hours at 4.4°C. Sensory evaluation and syneresis test were conducted in the end of each cycle to evaluate the effects of the freeze-thaw conditions to the sensory and physical characteristics of buko pie. A total of three freeze-thaw cycles were performed for each treatment. Results of the sensory evaluation showed that the 100% pre-gelatinized treatment was the most stable of the three. Incorporation of pre-gelatinized starch to the buko pie increases the capacity of the pasted starch molecules to hold water, even if it had undergone three freeze-thaw cycles. From the two-way analysis of variance test, there was o significant difference in the amount of water separated from each treatment during the freeze-thaw cycles. The freezing and thawing conditions did not greatly affect the separation of water from the samples